การพัฒนาต้นแบบระบบป้องกันผู้ป่วยพลัดตกจากเตียงโดยใช้เทคนิคการจำแนกท่าทาง - อมรรัตน์ แหวนเงิน (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Bed falling is prevalent in ageing patients. This research is, thus, designed to create a prototype system to prevent bed falling for ageing patients by using gesture recognition technique. This system will help nursing staffs to recognize the movement of patients which might lead to bed falling. The study was divided into three phases. The first phase of this study surveyed 289 targeted health personnel working at inpatient department in Hospitals in Bangkok under the Department of Medical, Ministry of Public Health. 90.7% of subjects were interested in the prototype system which helped identify bed falling. Moreover, the result showed that product features and mental, emotional and spiritual was related to the need of subjects with a level of significant at p = < 0.001 and 0.05 respectively. The second phase created a prototype using Gyro Sensors and Accelerometer Sensors to classify the posture and the position of the patients on the bed. The system is controlled by a microcontroller coded in C-language to transmit data through 2.4 GHz radio frequency signal transmission. The prototype will send the data to a server and create a warning sound when the patients movement is beyond the setup limit. The results showed that the prototype detected 5 gestures which were very vulnerable for bed falling. The final phase was to test technology acceptance and feasibility of product to commercialization. The study surveyed 30 targeted health personnel working at inpatient department, in hospitals in Bangkok under Department of Medical, Ministry of Public Health, and consumers who had to take care elderly at home regarding their chances of using the prototype in the house. The result showed that samples were interested in and willing to use the prototype because it was safe and could create a warning sound suddenly. In summaries, the prototype of bed falling prevention should be made available for market. From financial estimation, it is found that the price of the sale license should be about three hundred thousand baht with 10% of Royalty fee from estimation of profit. The investment will get of return in the 1st year where the total accumulated net cash flow is expected to be 412,000 baht. The prototype will first focus on hospital uses before extending to households in responses to better care, quality of life, and prepare for the aging society.